2003
DOI: 10.1001/archneur.60.4.483
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Complications of Anthrax

Abstract: A review of the literature suggests that the major neurologic symptom complex of infection by Bacillus anthracis is a fulminant and rapidly fatal hemorrhagic meningoencephalitis and that the reported initial mode of entry can be via the cutaneous or inhalation route. For febrile patients with acute neurologic deterioration with associated findings of dark necrotic pustules on the extremities, gram-positive rods in the cerebrospinal fluid, and multifocal areas of unexplained intracerebral hemorrhage on computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…In clinical studies, hemorrhage occurs in the draining lymph nodes, bowel segments, and meninges. 11,44,45 In animal models, hemorrhage was observed in mediastinal, mesenteric, and tracheobronchial lymph nodes, as well as in the meninges, lungs, and small intestinal serosas of B. anthracis-infected animals. 11 Because LT treatments induce hemorrhage, 14,46 these results might indicate that anthrax LT is involved in the hemorrhagic pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, hemorrhage occurs in the draining lymph nodes, bowel segments, and meninges. 11,44,45 In animal models, hemorrhage was observed in mediastinal, mesenteric, and tracheobronchial lymph nodes, as well as in the meninges, lungs, and small intestinal serosas of B. anthracis-infected animals. 11 Because LT treatments induce hemorrhage, 14,46 these results might indicate that anthrax LT is involved in the hemorrhagic pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Also CSF from lumbar puncture was positive for B. anthracis DNA by PCR Growth of the anthrax bacilli in CSF cultures is accepted as gold standard but it can take time (3). The major neurological complication of anthrax meningoencephalitis is mortal subarachnoid hemorrhages (5)(6)(7)(9)(10)(11). In the literature, the most common histopathological findings of anthrax meningoencephalitis are necrotizing vasculitis, cerebral infarction, edema, hemorrhagic meningitis, intraventricular hemorrhage, multifocal subarachnoid or intraparenchymal hemorrhages (3).…”
Section: Discussionmentioning
confidence: 99%
“…Anthrax meningitis/meningoencephalitis is the main neurological complication of anthrax infection and is associated with extremely high mortality despite antimicrobial therapy and supportive care (24,27). We have previously shown that B. anthracis Sterne is capable of invading brain endothelium in a process involving host actin cytoskeleton rearrangement to facilitate CNS entry (44); however, the basic pathogenic mechanisms by which B. anthracis penetrates the BBB have not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the spores germinate into vegetative bacteria, multiply, and then disseminate throughout the host, causing septicemia and toxemia (8). Systemic disease can be complicated by the onset of a fulminant and rapidly fatal hemorrhagic meningitis and meningoencephalitis (27). Anthrax meningitis is associated with a high mortality rate despite intensive antibiotic therapy (24).…”
mentioning
confidence: 99%